Overcoming localization of knowledge: The role of professional service firms - Stefan Wagner; Karin Hoisl; Grid Thoma (European School of Management and Technology (ESMT), 2013)
The literature on organizational learning asserts that external learning is often limited geographically and technologically. We scrutinize to what extent organizations acquire external knowledge by accessing external knowledge repositories. We argue that professional service firms (PSFs) grant access to nonlocalized knowledge repositories and thereby not only facilitate external learning but also help to overcome localization. Focusing on patent law firms, we test our predictions using a unique dataset of 544,820 pairs of EP patent applications. Analyzing patterns of knowledge flows captured in patent citations we find that accessing a PSF's repository facilitates the acquisition of external knowledge. As the effect is more pronounced for knowledge that is distant to a focal organization we conclude that having access to a knowledge repository compensates for localization disadvantages.
urn:nbn:de:101:1-2013091111538
Keywords: 650; Learning; knowledge acquisition; localization; patent citations; professional service firm